Inter-Species Comparison of Promoter Sequences of the Ets Transcription Factor PEA3 - Kann, Gregory (My University, 1999)
Chicken and pufferfish genomic libraries were screened with the intent of isolating PEA3 orthologues from evolutionarily removed vertebrate species. The chicken PEA3 gene was found to reside within 15 kb of genomic sequence, and approximately 2 kb of promoter sequence has been identified. Although the pufferfish PEA3 genomic sequence has yet to be completed, exons 2, 3, 4, 5, 12 and 13 have been found, and approximately 1 kb of sequence upstream of the putative start codon has been determined. In addition to the genomic sequence that was isolated, 5' RACE using pufferfish heart RNA produced a 334 bp cDNA sequence encompassing exons 2 to 5 of pufferfish PEA3. A pufferfish homologue of the human RNA helicase 1 (HRH1) gene was also found 3' of the PEA3 gene. Given that HRH1 is also found 3' of human PEA3 (E1AF) on chromosome 17q21, this finding would seem to indicate that chromosomal synteny is maintained between the human and pufferfish PEA3 loci. A four-way alignment of the mouse, human, chicken and pufferfish PEA3 promoters revealed that a region spanning from +1 to -260, relative to the transcriptional start site of mouse PEA3, is well conserved across the four promoters. Conserved transcription factor binding sites for SRY, HNF3β, NFY, AP-1, TCF, AP-2, v-myb, δEF1, and c-Ets-1 were found in three, and in some cases four of the promoters. An additional outcome of the pufferfish genomic library screen was the isolation of a pufferfish orthologue of the Ets transcription factor ERM. The relevance of these findings to the issue of transcriptional regulation of PEA3 expression is discussed.
Inter-species Comparison of the PEA3 Promoter
Keywords: species; promotor; sequence; transcription; PEA3; Ets